Midwive Competency Training Management Models in Health Promotion in Stunting-Based Prevention Collaborative Innovative Participation (Pilar) in West Nias District - Yati Simatupang, Mei; Gultom, Syawal; Rahman, Arif (Green Publisher, 2023)
A midwife is a woman who has completed a midwifery education program both domestically and abroad which is legally recognized by the Central Government and has met the requirements to practice midwifery. In carrying out their duties, midwives need good quality. Midwife competence is the ability and characteristics that include knowledge, skills and professional attitudes in carrying out their duties and work effectively that must be owned by a midwife, but in reality the midwife has not fully carried out her duties according to professional competency standards and gaps from ideal conditions and has not been carried out effectively. Midwives are health workers who are qualified to contribute to reducing maternal and child mortality and play a role in reducing stunting rates, this is because midwives are directly involved with women who are program objectives. Knowledge of midwives that has an impact on behavior where with good knowledge of midwives about stunting prevention, the better the knowledge of midwives, the better the quality of Ante Natal Care (ANC) services in preventing stunting. Training is a process of increasing systematically and in accordance with the needs of employees by increasing skills, knowledge and understanding as well as self-motivation. The development of a Participatory Innovative Collaborative (Pillar) training management model is an intervention model that has been analyzed, developed, tested, revised and implemented to obtain feedback that has an effect on the training objectives.